Effect of process parameters on the microstructure and mechanical properties of vacuum hot-press sintered Co-50 mass% Cr alloys. (8th August 2018) - Chang, Shih-Hsien; Chang, Chih-Yao; Huang, Kuo-Tsung; Wu, Ming-Wei
ABSTRACT: In the present research, two different compositions of submicron-structured cobalt (800 ± 45 nm) and chromium (700 ± 50 nm) powders are mixed to fabricate Co-50 mass% Cr alloys by the vacuum hot-press sintering technique. This study imposes various hot-press sintering temperatures (1150, 1200, 1250 and 1300°C) and pressures (20, 30, 40 and 50 MPa) while maintaining the sintering time at 1 h, respectively. The experimental results show that the optimum parameters of hot-press sintered Co-50 mass% Cr alloys are 1200°C at 50 MPa for 1 h. Meanwhile, the sintered density reaches 7.73 g cm −3, the closed porosity decreases to 0.31%, and the hardness and transverse rupture strength values increase to 80.6 ± 0.3 HRA and 1052.9 ± 17.5 MPa, respectively. Grain growth is not obviously generated after 1200°C hot-press sintering at 50 MPa for 1 h. Consequently, the optimal solid-phase sintering process effectively improved hot-press sintered Co-50 mass% Cr alloys, which resulted in the good properties.